2006
DOI: 10.1088/0953-4075/39/12/016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the (e, 2e) single ionization of He and Ar at large energy loss close to minimum momentum transfer

Abstract: We report new coplanar (e, 2e) measurements for ionization of He and Ar under kinematics characterized by large energy transfer and close to minimum momentum transfer from the projectile to the target. These kinematics have remained rather unexplored to date due to the smallness of the corresponding cross sections. They could be investigated here thanks to the high sensitivity of our multi-collection spectrometer. The experimental results are used as a sensitive test of state-of-the-art available theoretical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 44 publications
5
30
0
Order By: Relevance
“…Another recent line of (e,2e) research explored the valence shell ionization of noble gas atoms at a larger incident energy with the ejected electron detector being tuned to 500 eV (Catoire et al 2006. As compared to a lower Figure 1.…”
mentioning
confidence: 99%
“…Another recent line of (e,2e) research explored the valence shell ionization of noble gas atoms at a larger incident energy with the ejected electron detector being tuned to 500 eV (Catoire et al 2006. As compared to a lower Figure 1.…”
mentioning
confidence: 99%
“…Considering very weak beams were used, our TDCS have large statistical uncertainties and there is data scatter. To aid in comparing with theory and in interpreting the data, the data were fitted with an empirical model using a double peak structure that was first noted by Ehrhardt et al [10] in TDCS data for argon and was later observed in other electron impact studies [11][12][13][14], as well as in a higher energy study we reported [5]. The two peak structures were attributed to the p outer-shell structure of argon.…”
Section: Data Fitsmentioning
confidence: 99%
“…The two peak structures were attributed to the p outer-shell structure of argon. We applied the model, which consisted of two binary and two recoil components, by fitting experimental data [11][12][13] and theoretical DWBA and CDW predictions [1,8,[14][15][16], where a double peak structure was resolved or nearly resolved, and also by fitting to kinematic conditions, where only a single broad lobe was observed. Fits to the theoretical calculations, where the components were resolved, showed that the FWHM for the two binary components systematically decreased as a function of momentum transfer, e.g., for q = 0.2 a.u., the FWHM was ~90°; for q = 0.75 a.u., it was ~50°.…”
Section: Data Fitsmentioning
confidence: 99%
“…The final state is reduced to a three-body system by assuming that the residual ion (Na + ) acts as a point charge on the two escaping electrons. Such an approximation is, of course, not generally adequate [10,11], but it allows us to apply the DS3C or 3C model to the complex case of ionizing a many-electron atom such as sodium in the present case or carbon [13], argon [14], and neon [15], or a complex molecule such as water [16]. We might expect that our DS3C or 3C model would yield at least qualitatively correct results, for instance, concerning the positions of the binary and recoil lobes maxima.…”
Section: Theoretical Treatmentsmentioning
confidence: 99%